Environmental regulation and competitiveness: Evidence from Romania - Guglielmo Maria Caporale; Christophe Rault; Robert Sova; Anamaria Sova (Institute for the Study of Labor (IZA), 2010)
According to the pollution haven hypotheses differences in environmental regulation affect trade flows and plant location. Specifically, environmental stringency should decrease exports and increase imports of dirty goods. This paper estimates a gravity model to establish whether the implementation of more stringent regulations in Romania has indeed affected its competitiveness and decreased exports towards its European trading partners. Our findings do not provide empirical support to the pollution haven hypothesis, i.e. environmental stringency is not found to affect significantly total trade, or its components (pollution intensive trade and pollution intensive trade related to non-resource-based trade).
Keywords: F14; Q28; 330; Environmental stringency; competiveness; gravity model; Umweltpolitik; Wirkungsanalyse; Außenwirtschaft; Internationaler Wettbewerb; Gravitationsmodell; Schätzung; Rumänien